Symmetry of Shank Muscle Strength, Passive Stiffness and Plantar Pressure Following IASTM Accompanied by Electrotherapy in a Case with Severe Ankle Stiffness - Mousavi, Seyed Hamed; Khorramroo, Fateme; Minoonejad, Hooman (Journal of Sports Medicine and Therapy, 2024)
Excessive ankle stiffness can greatly impact mobility, leading to discomfort, difficulty in walking, and limited Range of Motion (ROM). We aimed to identify and address the symmetry of shank muscle strength, ankle passive stiffness, and plantar pressure distribution, in a patient with unilateral excessive ankle stiffness, utilizing Instrument-Assisted Soft Tissue Mobilization (IASTM) accompanied by Faradic Electrical Stimulation (FES). The patient’s muscle strength and ROM which had diminished due to 3.5 years of ankle immobilization post-rescue from amputation, underwent a 12-week program involving IASTM and FES. The plantar and dorsiflexion muscles’ torque, ROM, and plantar pressure were measured using an isokinetic and plantar distribution system before and after the intervention. Symmetry of muscle torque, ROM, and plantar pressure between two limbs were calculated for pre and post-test. Results indicated improvement in the ratio index of the concentric/eccentric dorsi- and plantar-flexion peak torque and dorsi- and plantar-flexion work, ROM, gait line length, and contact time after a 12-week intervention. The study suggests that IASTM and FES are effective interventions for restoring symmetry in a patient with post-operation complications, highlighting the need for further research on similar cases.